2019
DOI: 10.1002/mnfr.201900117
|View full text |Cite
|
Sign up to set email alerts
|

High‐Fat Diet Enriched with Bilberry Modifies Colonic Mucus Dynamics and Restores Marked Alterations of Gut Microbiome in Rats

Abstract: Scope Emerging evidence suggests that high‐fat diet (HFD) is associated with gut microbiome dysbiosis and related disorders. Bilberry is a prebiotic food component with known health benefits. Herein, the dynamics of the colonic mucus layer and microbiome during HFD and bilberry supplementation are addressed. Methods and results The effects on colonic mucus thickness in vivo and gut microbiota composition (Illumina sequencing, quantitative real‐time PCR) are investigated in young rats fed a low‐fat diet or HFD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Consumption of the high-fat diet ad libitum resulted in vastly different mucosal and faecal microbiota community structures (Fig. 2) and compositions (Table S2) compared to the NC group, this was consistent with previous reports on alterations in the gut microbiota upon consumption of a high-fat diet [24,37,38]. While fasting did not reverse all high-fat diet-induced modifications, it changed the abundance of specific gut bacteria, including ASVs in the families Christensenellaceae, Lachnospiraceae and Ruminococcaceae, which have been previously linked with the intake of a high-fat diet and obesity in mice [24,38].…”
Section: Fasting Induced Diet-specific Changes In the Mucosal And Fae...supporting
confidence: 92%
“…Consumption of the high-fat diet ad libitum resulted in vastly different mucosal and faecal microbiota community structures (Fig. 2) and compositions (Table S2) compared to the NC group, this was consistent with previous reports on alterations in the gut microbiota upon consumption of a high-fat diet [24,37,38]. While fasting did not reverse all high-fat diet-induced modifications, it changed the abundance of specific gut bacteria, including ASVs in the families Christensenellaceae, Lachnospiraceae and Ruminococcaceae, which have been previously linked with the intake of a high-fat diet and obesity in mice [24,38].…”
Section: Fasting Induced Diet-specific Changes In the Mucosal And Fae...supporting
confidence: 92%
“…Several studies have reported that HFD can disrupt the intestinal barrier function by decreasing the number of colonic epithelial cells and goblet cells and increasing the infiltration of inflammatory cells, which triggers intestinal oxidative stress. [ 38‐40 ] In this study, the histological analysis revealed that the MG group exhibited a decrease in the number of colonic epithelial cells with concomitant infiltration of the white inflammatory cells. The supplementation of Vc or LCP can repair the colonic epithelium.…”
Section: Discussionmentioning
confidence: 64%
“…These direct effects of bilberry anthocyanins may well contribute to the effects observed in the current study. In addition, bilberry polyphenols may alter the gut microbiome and thus secondarily influence the response to obesity-inducing diets [ 32 , 56 , 57 , 58 ]. Further studies are needed to understand the effective constituents of bilberry and their detailed mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%